Implementation of Molecular Surveillance After a Cluster of Fatal Toxoplasmosis at 2 Neighboring Transplant Centers. (19th May 2016) - Isa, Flonza; Saito, Kohta; Huang, Yao-Ting; Schuetz, Audrey; Babady, N. Esther; Salvatore, Steven; Pessin, Melissa; van Besien, Koen; Perales, Miguel-Angel; Giralt, Sergio; Sepkowitz, Kent; Papanicolaou, Genovefa A.; et al.
Abstract : After a cluster of fatal toxoplasmosis among stem cell transplant recipients at 2 hospitals, surveillance with polymerase chain reaction (PCR) (blood) was instituted. Rate of reactivation among seropositive recipients was 2.2 and 16%. Parasitemia was successfully managed with preemptive treatment. For seropositive recipients unable to take prophylaxis, toxoplasma PCR surveillance should be routinely performed.